2000
DOI: 10.1007/pl00009907
|View full text |Cite
|
Sign up to set email alerts
|

Existence of multipeak solutions for a semilinear Neumann problem via nonsmooth critical point theory

Abstract: We study a perturbed semilinear problem with Neumann boundary conditionwhere Ω is a bounded smooth domain of R N , N ≥ 2, ε > 0, 1 < p < N +2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 22 publications
1
68
0
Order By: Relevance
“…Mountain pass solutions, for example, possess a maximum point M ε at ∂ such that H (M ε ) → max M∈∂ H (M), where H is the mean curvature of ∂ . This result as well as the uniqueness of M ε was established in [32,33] and motivated the search of more general solutions of (P ε ) concentrating at critical points of H ; see [12,17,18,19,26,31,34,41].…”
Section: Introductionmentioning
confidence: 86%
“…Mountain pass solutions, for example, possess a maximum point M ε at ∂ such that H (M ε ) → max M∈∂ H (M), where H is the mean curvature of ∂ . This result as well as the uniqueness of M ε was established in [32,33] and motivated the search of more general solutions of (P ε ) concentrating at critical points of H ; see [12,17,18,19,26,31,34,41].…”
Section: Introductionmentioning
confidence: 86%
“…It has been proved that higher energy solutions exist, which concentrates at one or several points of the boundary, or at one or more points in the interior, or a combination of the two effects. See [5], [4], [11]- [8], [20]- [17], [23]- [24], [39], [45]- [46]- [26] and the references therein. In particular, Lin, Ni and Wei [26] showed that there are at least C N ( | log |) N number of interior spikes.…”
Section: Introduction and Statement Of Main Resultsmentioning
confidence: 99%
“…As in the subcritical case the least energy solution blows up, as μ goes to infinity, at a unique point which maximizes the mean curvature of the boundary [3], [42]. Higher energy solutions have also been exhibited, blowing up at one [2], [55], [48], [26] or several separated boundary points [41], [37], [56], The above conjecture was studied by Adimurthi-Yadava [4], [5] and Budd-KnappPeletier [11] in the case Ω = B R (0) and u radial. Namely, they considered the following problem: Theorem A ( [4], [5], [6], [11]).…”
Section: Introductionmentioning
confidence: 99%